USING KEY PERFORMANCE INDICATORS AT WORK WITH THE CUSTOMS REPRESENTATIVE - D. Afanasenko; N. Barkova; A. Tkhai (Вестник университета)
One of the well-known tools of employee motivation are key performance indicators. Key performance indicators help to determine how effectively the work has been carried out by an employee, division, or the company as a whole. Currently, key performance indicators are using in various spheres of public life, as this motivational tool has shown its high efficiency. The key performance indicators on the example of assessing the work of the customs representative have been considered in the article. The main indicators on which it is possible to carry out an assessment of work of the customs representative have been chosen. Examples of calculation of remuneration with use of indicators of key performance indicators have been provided.